A core of macrophages facilitates ovarian cancer metastases - Freire Valls, Aida; Shen, Ying; Schmidt, Thomas (Translational cancer research, 2017)
The study of Yin et al. focuses on the underlying mechanisms of ovarian cancer (OC) metastases. During OC progression, tumor cells detach from the primary tumor and interact with tumor-associated macrophages (TAMs) to survive in the peritoneal fluid as free-floating spheroids. TAMs provide matrix support and growth factors in the core of the tumor spheroid in the initial steps of peritoneal carcinomatosis. Here the EGF/EGFR signaling axis establishes TAM-tumor cell crosstalk as a critical paracrine loop to support tumor proliferation and anoikis protection. By using EGFR inhibitors or monoclonal antibodies survival of OC tumor bearing mice was improved. While this indicates new strategies to treat peritoneal metastases and to potentially improve OC patient prognosis, targeted therapies against the EGF receptor failed in the clinical setting. Future trials will need to elucidate if different treatment regimes could still use this promising target. Moreover, the EGF/EGFR crosstalk induces autocrine VEGF-C/VEGFR-3 signaling in tumor cells. This is important for tumor cell migration and ICAM-1 upregulation that in turn maintains cell-cell contact between tumor cells and TAMs (via CD11b/c), thereby stabilizing the tumor spheroids. The importance of TAMs was confirmed in 128 analyzed spheroid patient samples, where a high percentage of macrophages within spheroids were associated with a lower overall survival (OS) of OC patients. In this perspective we discuss the findings of Yin et al. and speculate on (chemo)protective properties of OC spheroids, the general role of macrophages, macrophage recruitment and tumor cell-macrophage interaction. We highlight the current status of the proposed targeted therapies and propose future clinical application.
Gesehen am 09.04.2018